URGENSI INTELIGENSI BESERTA AFIRMASI BAGI PENDIDIKAN DAN PEMBELAJARAN - I Made Ariasa Giri; Ketut Agus Nova (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2022)
Intelligence is a psychological attribute that has a very important role in the educational process, especially science and practice of Guidance and Counseling. The results of intelligence measurements are a picture of previous education that has been achieved, and can also be a predictor (forecasting tool) to the results of education in the future, especially with regard to the selection of prospective students or students who exceed the limits of school or college. But it must be realized that not all intelligence tests are suitable to be used as a tool to predict because there are many factors that can affect the suitability of the application. It must also be realized in predicting a success in learning that learning itself is not merely the utilization of potential abilities (intelligence), but there are still many factors that help determine the outcome of the learning process. Success in learning can reflect intelligence or is a reflection of assessing a student's intelligence capacity. The higher a person's level of intelligence, the more likely the higher the success of learning achieved. Basically intelligence has a very big relationship to the success of the person in learning something. Therefore, intelligence is very related to the learning ability of students in school or on campus.Keywords: Intelligence, Education, Learning